Penerapan Fungsi-Fungsi Manajemen Gereja Alkitabiah Pada Masa Kini: Sebuah Analisis Historis-Biblikal - Yeremia; Adella, Selvi; Yulita; Kisara, Randa (Sekolah Tinggi Teologi Sriwijaya, 2025)
The development of modern management requires the church to renew its management practices. There are pros and cons regarding whether the church can adopt modern management models that are considered profit-oriented. Nevertheless, this writing aims to present management that is not only centered on church officials but also on the management functions outlined in the Bible to be understood and applied in today's church. The research method used is literature study utilizing historical-biblical analysis by examining literature sources from various online articles. The results of the study find that the management functions outlined in the Bible, particularly in the New Testament, such as administrative function, governance function, and servanthood function, still need to be reinterpreted and applied by all members of the body of Christ serving in the church, especially church officials.